Tucker, Grant. Interview about growing up in New Perlican and the goats in the community. - Barrett, Terra (2017)
Terra Barrett of the Heritage Foundation of Newfoundland and Labrador interviews Grant Tucker about growing up, goat memories and keeping a pet goat as part of The Goats of New Perlican Oral History Roadshow Project in partnership with Heritage New Perlican.